The Effects of Capital Campaigns on Other Nonprofits' Fundraising. Issue 3 (3rd February 2017) - Woronkowicz, Joanna; Nicholson‐Crotty, Jill
Abstract : This study focuses on the effects of capital campaigns on the fundraising performance of other nonprofits within the same geographic region. Drawing from research in organizational ecology and charitable giving, we offer a theory of capital campaign impact that says any impact of a campaign must be looked for in a carefully circumscribed area or population of organizations, and that campaigns raise awareness of the need for services within a particular area. We use data on capital campaigns at arts nonprofit organizations in forty‐eight counties across the United States between 1999 and 2007, coupled with financial data on nonprofits in the arts in the same county to test our hypotheses. The results from our analyses show that a major capital campaign positively affects other nonprofits' fundraising, and the effect varies depending on the phase of the capital campaign. We discuss possible mechanisms that drive the positive effects of capital campaigns, and conclude with a short illustration.